STRENGTH SIMULATION AND TOPOLOGY OPTIMIZATION DESIGN OF OFF-ROAD VEHICLES’ HUB MOTOR HOUSING - QI Chang; MA Yuanhang; YANG Lining; YANG Shu; WANG Bolong (Jixie qiangdu)
Aiming at the issues of fracture and weight reduction in the wheel hub motor housing of an off-road vehicle, a structural strength finite element simulation analysis and structural topology optimization design were conducted. Firstly, a multi-body dynamics model of the entire vehicle was established, and a simulation analysis was performed to determine the load boundary conditions of the hub motor housing. Secondly, based on the spatial position relation between the housing and interconnected structures, a finite element model of the motor housing and suspension system was constructed for dynamic simulation analysis. Subsequently,using the OptiStruct software platform,with the objective of minimizing structural compliance and constraints on volume ratio before and after optimization as well as the maximum stress, a mathematical topology optimization model for the motor housing under various typical operating conditions was established and solved to obtain the optimal material distribution scheme. Finally, the optimization results were verified by simulation. The results indicate that compared to the existing design,the optimized hub motor housing structure experiences a stress reduction of over 40% and a weight reduction of 2.6%. It addresses the original fracture issue and eliminates the phenomenon stress concentration, thus providing the valuable reference for the design of similar hub motor housing structures.